The importance of ultrasound in staging and gaining a pathological diagnosis in patients with lung cancer—a two year single centre experience. Issue 5 (25th February 2011) - Hoosein, M M; Barnes, D; Khan, A N; Peake, M D; Bennett, J; Purnell, D; Free, C; Entwisle, J J
Abstract : Background: Initial studies on the use of ultrasound in the detection and sampling of supraclavicular lymph nodes in patients with suspected lung cancer show this to be a promising technique, giving both a cytological diagnosis and pathological N3 (pN3) stage. Leicester published its initial experience in 2005 and the aim of this study was to establish if this had been embedded into the diagnostic pathway, and further to examine the use of ultrasound in diagnosing and staging lung cancer by imaging other areas including pleural effusions, chest wall, bone and liver lesions. Methods: All patients diagnosed with lung cancer, registered on the Leicester lung cancer database over a two year period between January 2007 and December 2008, had their imaging and pathology retrospectively reviewed; 996 primary lung cancer patients were identified (n=996). Of these, 318 patients underwent an ultrasound examination (n=318), consisting of ultrasound of the neck, pleural cavity, and metastatic lesions potentially amenable to ultrasound guided aspiration/biopsy. Results: The overall malignant yield was 45% of patients scanned (95% CI 39.5% to 50.4%) and 81.3% of patients sampled (95% CI 75.5% to 87%). Of the 996 patients, 14.4% (n=143) had a positive ultrasound guided cytological diagnosis (95% CI 12.2% to 16.5%). Of all the pathological diagnoses (n=765), 18.7% were ultrasound guided (95% CI 15.9% to 21.5%). In particular, 32.2% of patients with CT detected neck or mediastinal nodes had a diagnosis and stage achieved by neck ultrasound. Conclusion: The use of ultrasound gives a rapid and less invasive method of diagnosing and staging lung cancer and has become embedded into the diagnostic pathway. We advocate its increased use and availability in patients with lung cancer.